Regulation of T Cell Responses by Nano-Hydroxyapatite to Mediate the Osteogenesis - Guo, Fangze; Yuan, Changqing; Huang, Hailin; Deng, Xuyang; Bian, Zirui; Wang, Danyang; Dou, Keke; Mei, Li; Zhou, Qihui (Frontiers in Bioengineering and Biotechnology, 2022)
Nano-hydroxyapatite (nHA) has been widely applied as a tissue-engineering biomaterial and interacted with osteoblasts/stem cells for the repair of bone defects. In addition, T cells that coexist with osteoblasts/stem cells in the bone modulate the regulation of osteoimmunology by cytokine formation. However, the effects of nHA on T cells and the following regulatory interplay on osteogenic differentiation have been rarely examined. In this work, the physicochemical properties of needle-like nHA are characterized by field emission scanning electron microscopy, zeta potential, Fourier transform-infrared and X-ray diffraction. It is found that as the concentration of nHA increases, the proliferation of T cells gradually increases, and the proportion of apoptotic T cells decreases. The percentage of CD4+ T cells is higher than that of CD8+ T cells under the regulation of needle-like nHA. Furthermore, the supernatant of T cells co-cultured with nHA significantly inhibits the osteogenic differentiation of MC3T3-E1 by downregulating the formation of alkaline phosphatase and calcium nodule compared with the supernatant of nHA. Thus, our findings provide new insight into the nHA-mediated T cell and osteoblast interactions.